THE EFFECT OF THE PREVIEW, QUESTION, READ, SUMMARIZE, AND TEST (PQRST) TECHNIQUE PLUS CHARACTER JOURNAL ENTRIES (CJE) PROJECT TOWARDS STUDENTS’ READING COMPREHENSION - Zetira, Yoanda; Yuliana, Yohanes Gatot Sutapa; Surmiyati, Surmiyati (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study employed a pre-experimental research design to determine the effectiveness of using the Preview, Questions, Read, Summarize, and Test (PQRST) technique plus Character Journal Entries (CJE) in teaching reading comprehension of narrative texts. The participants of this research were SMA Negeri 9 Pontianak students in the tenth-grade students, consisting of 252 students in academic 2023/2024. The sample was chosen using cluster random sampling facilitated by the Spinning Wheel website. The study’s sample consisted of 30 students from X E. This research used a test as its instrument. The test consisted of 20 multiple types of questions. The calculation was done using SPSS v.23. The researcher used the Wilcoxon Signed Ranks Test for the paired test. The result shows the Asymp.Sig (W) value (0,000) < W table (critical values table) (0,05). As a result, the null hypothesis was rejected, and the alternative hypothesis was accepted, meaning the PQRST technique plus CJE project has been significantly effective towards students’ reading comprehension, with the result of effect size 2,45.